Glycemic Control in Type 2 Diabetes Mellitus and its Association with Duration of Diabetes & Glycosylated Hemoglobin A1 (Medical Forum Monthly, 2024)
Objective: The aim of present study was to evaluate glycemic control in type 2 diabetes mellitus (DM) subjects and its association with the duration of diabetes & glycosylated Hemoglobin A1 (HbA1c).Subjects and Methods: A descriptive study, comprising of 571 diagnosed cases of type 2 DM were studied at the Diabetic clinic of Isra University/ consultant private clinics over a year period. Diabetic subjects were divided as; controlled diabetics (Group I. HbA1c ≤7%) and uncontrolled diabetics (Group II. HbA1c >7%). The data was recorded on a proforma. Blood glucose was measured by glucose oxidase method & HbA1c on automated clinical chemistry analyzer. The student`s t-test and chi-square were used for the quantitative and qualitative data respectively. Spearman`s correlations was used for a linear correlation of HbA1c with the duration of DM and random blood sugar (RBS). The data was analyzed on SPSS version 16.0 for windows. P-value at ≤ 0.05 was taken statistically significant.Results: The mean age was noted as 45.8±7.4 & 43.2±9.0 years (p=0.001) & male to female ratio of 2:1 & 0.9:1 in both groups respectively. RBS was elevated in 169 (66%) and 211 (66.9%) in both groups respectively (p=0.74). Poor glycemic control was observed in 315 (55.1%) of subjects. Of 571 T2DM, 256 (44.8%) were having HbA1c <7% (Group I.) and 315 (55.2%) HbA1c ≥7% (Group II). The HbA1c values as high as ≥13.1% was noted in 73 (12.7%). A highly significant difference was observed in HbA1c (p=0.0001) between groups. Significant correlation of HbA1c was found with duration of DM (r=0.65, p=0.0001) but not with the RBS (r=0.038, p=0.36)Conclusion: We report poor glycemic control as indicated by glycosylated Hb A in type 2 diabetics. Public campaigns be attempted on regular basis to make diabetics aware of glycemic control.